Bacterial Succession on Sinking Particles in the Ocean's Interior - Pelve, Erik A.; Fontanez, Kristina M.; DeLong, Edward F. (Frontiers in Microbiology, 2017)
Sinking particles formed in the photic zone and moving vertically through the water column are a main mechanism for nutrient transport to the deep ocean, and a key component of the biological carbon pump. The particles appear to be processed by a microbial community substantially different from the surrounding waters. Single cell genomics and metagenomics were employed to describe the succession of dominant bacterial groups during particle processing. Sinking particles were extracted from sediment traps at Station Aloha in the North Pacific Subtropical Gyre during two different trap deployments conducted in July and August 2012. The microbial communities in poisoned versus live sediment traps differed significantly from one another, consistent with prior observations by Fontanez et al. (2015). Partial genomes from these communities were sequenced from cells belonging to the genus Arcobacter (commensalists presumed to be associated with protists such as Radiolaria), and Vibrio campbellii (potential pathogens known to be associated with crustacea). These bacteria were associated with the particle-associated community at specific depths in both trap deployments, presumably due to their specific host-associations. Partial genomes were also sequenced from cells belonging to Idiomarina and Kangiella that were enriched in live traps over a broad depth range, and represented a motile copiotroph and a putatively non-motile algicidal saprophyte, respectively. Planktonic bacterial cells most likely caught in the wake of the particles belonging to Actinomarina and the SAR11 clade were also sequenced. Our results suggest that similar groups of eukaryote-associated bacteria can be consistently found on sinking particles at different times, and that particle remineralization involves specific, reproducible bacterial succession events in oligotrophic ocean waters.